Efektivitas Pembelajaran Bahasa Indonesia Bagi Penutur Asing di KBRI Finlandia - Mahmud, Mahmud; Jaufillaili, Jaufillaili (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to investigate the effectiveness of Bahasa Indonesia for non native speakers teaching process in the Finland Embassy based on the students perception through survey method. This study means to give the descriptive information about the teaching process held in 2018. The subject of this research is all the participant of the BIPA program. The instrument of the research is Course Experience Questionnaire (CEQ) by Ramsden (1993) which includes; Teaching Quality, Generic Skills, Students motivation, Academic environment, Assessment, and Curriculum. The data is analyzed by using psicometric Likert scale. The result of the study show; Teaching Quality is categorized effective, Generic skills is categorized less effective, Students motivation is categorized effective, Academic environment is categorized quite effective, Assessment is categorized quite effective, and Curriculum is categorized not effective. Overall, the process of the BIPA teaching activity is categorized quite effective.